Reconstruction of the Concept of Restorative Justice of the Criminal Justice System in Indonesia - Heksa Koes Raharjo Bambang Sasmoyo Suryoningrat; Muhammad Rustamaji (MultiTech Publisher, 2023)
Restorative justice is basically an approach to criminal law that contains a number of traditional values. This is based on two indicators, namely the values on which it is based and the mechanisms it offers. This is the basis for considering why the existence of restorative justice is being taken into account again. The existence of this approach is perhaps as old as criminal law itself. Apart from imprisonment which has consequences for the prisoner's family, the current system is seen as not providing relief or healing to the victims. Moreover, the legal process takes a long time. In contrast, in the restorative model the emphasis is on conflict resolution. This idea of Restorative Justice has also been accommodated in the Criminal Code Bill, namely the introduction of an alternative criminal system in the form of social work sentences and supervision sentences. So that in the end, Restorative Justice pays attention simultaneously to the interests of crime victims, crime perpetrators and society.